Pemberdayaan Masyarakat Dalam Mempersiapkan Desa Wisata Air di Desa Wanasari - Rahayu, Sri; Firmansyah, Refi; Irpan, Nurul; Haq, Shidqi Amirul; Mutaqin, Ridwan; Sanusi, Ahmad; Koswara, Reyhan Rizqia; Noerkemalasari, Dylla; Laeli, Sasya Riwani Al; Husna, Rida Sofiatu; Rahmana, Wiguna; Aripin, Adi Muhammad; Ahkop, Irsal Adil; Gunawan, Latif; Marsalina, Sali; Aprilianti, Mega; Mustika, Lesti; Raihandika, Hisyam; Farwati, Aida; Riswandi, Muhamad; Prilangga, Regi (Institut Teknologi Garut, 2022)
One of the goals of community empowerment is to support regional development through improving the quality of human resources and the wise and responsible use of natural resources towards competitive advantage in local, regional and global competition. Community empowerment is carried out through the Garut Institute of Technology Real Work Lecture program in an effort to increase and foster a sense of student empathy for the conditions of society and its environment, in order to be able to solve problems experienced by the community. With the plan to have a Water Tourism Village in Wanasari Village, Group 3 KKN students participate by carrying out various work programs such as making signposts for directions and naming several location points on Google maps as a way to make it easier to find the location of a Water Tourism Village in the future. Implementation of each work program in preparing for the Water Tourism Village, students always involve the community in order to increase the participation, knowledge and skills of the community. The implementation of the activities of each work program is divided into four method stages. The first stage is location observation and problem identification, the second stage is problem solving formulation, the third stage is implementation of activities in the field, the fourth stage is evaluation and monitoring for corrections and improvements to program sustainability. Activities are carried out after students hold hearings with village officials and community leaders, so that the priority scale of activities is determined based on the conditions and potential that exist in the Wanasari Village community. As many as 41% of the total 3,902 residents of Wanasari Village gave a good response to the Group 3 KKN Student work program.